Importance of Skill Development and Training in the Vocationalization of Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Training in vocational fields, such as construction or manufacturing, is a critical part of our educational strategy. The objective of the study is to examine the current vocational education, training, and skill development sector regulatory system, extent of future work in Ranchi Jharkhand’s area of vocational education, training, and skill development. Questionnaires and structured interviews are used to gather data in surveys. It is possible to will be collect data in two ways: first, will be using original data, and second, will be using secondary data collected from other sources. Both types of data will be essential for the study's completion and to arrive at an impartial result and they will be being utilized. The researcher spent over two or three years digging into the topic of Vocational Training and Development, finding issues with administration, regulations, plans, policies, and standards as well as with governance and regulation.